2008
DOI: 10.1021/jp8052295
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Mechanisms of C−H Bond Activation by a Doubly Charged Metal Ion: Guided Ion Beam and Theoretical Studies of Ta2++ CH4

Abstract: A guided ion beam tandem mass spectrometer is used to study the kinetic-energy dependence of doubly charged atomic tantalum cations (Ta(2+)) reacting with CH4 and CD4. As for the analogous singly charged system, the dehydrogenation reaction to form TaCH2(2+) + H2 is exothermic. The charge-transfer reaction to form Ta(+) + CH4(+) and the charge-separation reaction to form TaH(+) + CH3(+) are also observed at low energies in exothermic processes, as is a secondary reaction of TaCH2(2+) to form TaCH3(+) + CH3(+).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 59 publications
4
42
0
2
Order By: Relevance
“…The scattering investigation of the analogous reaction leading to NO + + N + + O [48] showed very similar results and led to the conclusion that Reaction (20) proceeded by a similar mechanism as Reaction (19), namely,…”
Section: Reactions Of N 2þmentioning
confidence: 80%
See 1 more Smart Citation
“…The scattering investigation of the analogous reaction leading to NO + + N + + O [48] showed very similar results and led to the conclusion that Reaction (20) proceeded by a similar mechanism as Reaction (19), namely,…”
Section: Reactions Of N 2þmentioning
confidence: 80%
“…LaFe 2+ YFe 2+ ) and alkanes were described, too [16]. Guided-beam and theoretical studies of reactions between Ta 2+ and methane [19] provided information on bond energies of the species involved, mapped the potential energy surfaces and intermediates and suggested that the products were formed through a H-Ta 2+ -CH 3 intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Most of these reactions are driven by the radicaloid nature of the oxide cations with the spin mostly located on oxygen, which leads to a high preference for hydrogen-atom abstraction from methane to generate methyl radicals. This situation is in contrast to the dehydrogenation of methane by various 5d elements to give metal carbenes MCH 2 + , [6,11] or MCH 2 2+ , [6,12] and to the C À C coupling reactions with methane observed for medium-sized hydrocarbon dications, [13] in which the dehydrogenation takes place with the "CH 2 " fragment remaining at the ionic species.…”
mentioning
confidence: 83%
“…Other dipositive metal ions that have been shown to similarly activate methane include Zr 2+ , Nb 2+ , Ta 2+ , 34,39 and Th 2+ . 40 It should be noted that thermal Hf + ions are unreactive with CH 4 and the dehydrogenation reaction to form HfCH 2 + is endothermic, this in contrast to most third-row transition metal ions, as discussed by Armentrout and co-workers.…”
Section: +mentioning
confidence: 99%